Salmonellatyphi and endocarditis: a systematic review of case reports - Jabeen, Kokab; Bint Ali, Sameen; Tufail, Zainab; Mustafa, Sana; Chaudhry, Mahnoor; Tahir, Muhammad J.; Asghar, Muhammad Sohaib; Ahmed, Ali (Frontiers in Medicine, 2024)
Introduction Salmonella typhi, a gram-negative bacterium responsible for typhoid fever, can infect the inner lining or valves of the heart and cause endocarditis. This systematic review aimed to report cases of S. typhi-associated endocarditis and its clinical features. Methods This systematic review was reported as per the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) checklist. Only case reports and case series of endocarditis caused by S. typhi, irrespective of age, gender, and demographics, were considered eligible for inclusion. To identify relevant studies, a literature search was conducted using relevant keywords on PubMed, Google Scholar, and the Cochrane Library from inception to 31 December 2023. After selecting the studies, the relevant data were extracted and pooled in terms of frequencies and percentages. A quality assessment was performed using the Joanna Briggs Institute Critical Appraisal Checklist for Case Reports. Results This review included seven case reports, comprising 22.2% female and 77.8% male patients. The mean age of patients was 27.9 + 12.0 years. Regarding past medical history, 33.3% (3/9) of patients had a previous cardiac pathology. Fever remained the most common complaint, occurring in 88.9% of cases. Transthoracic and transesophageal echocardiography were used to diagnose all cases, with 33.3% identifying vegetation on the mitral, aortic, and tricuspid valves. Ceftriaxone, with or without gentamycin, remained the choice of antibiotic for 88.9% of cases, and all patients responded to the offered treatment. Conclusion S. typhi-associated endocarditis, though rare, presents unique challenges and requires timely diagnosis. This systematic review of seven cases highlights a predominantly male population affected, with a mean age in the third decade, suggesting a higher invasiveness than other causes. The findings from this study underscore the importance of early recognition and appropriate management, primarily with antibiotic therapy. Further research with larger cohorts is crucial to refine understanding and guide policymaking for this rare but life-threatening condition.